Effects of Writing Interventions on the Level and Trend of Total Words Written: A Meta-Analysis. (January 2022) - Datchuk, Shawn M.; Rodgers, Derek B.; Wagner, Kyle; Hier, Bridget O.; Moore, Christopher T.
We estimated effects of writing interventions on the level and trend of writing fluency—rate of total words written over time—by students with and without disabilities. Using mixed-effects regression and an information-theoretic ranking of competing models, we synthesized results of 42 single-case experimental design studies with a total of 205 students. A variety of acquisition and fluency interventions were used across studies, such as self-regulated strategy development and timed practice with performance feedback. We found acquisition and fluency interventions produced an increase in level and a gradual increase in trend of total words written per minute. Students receiving fluency intervention tended to have higher levels of performance across experimental phases (i.e., baseline, intervention, and postintervention), but students receiving acquisition had steeper upward trends. In addition, we found higher levels of total words written per minute on writing tasks with brief time limits (i.e., ≤10 min) and in the writing of older students.